MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA KATOLIK MENGGUNAKAN MEDIA KOMIK ALKITABDI KELAS III SD INPRES LISABETHO - Kresensia Adel Goma (Yayasan Akrab Pekanbaru, 2019)
This classroom action research aims to improve the learning outcomes of Catholicism by using Bible comics. This Classroom Action Research (CAR) was conducted in two cycles using the spiral method developed by Kemmis and Tagart in class III students conducted at the Lisbon SDInpres. From the Classroom Action Research (CAR) activities, it is known that the research subjects (class III students) obtain improved learning outcomes. In the first cycle, the implementation of which was carried out conventionally, the average learning outcomes only reached 68.39 (under the KKM). Whereas in the second cycle, the learning action was carried out using the media 'Bible Comics', the average reached 86.10 or up 17.71 from the cycle I. The conclusion of this study is that the use of 'Bible Comics' media learning can improve learning outcomes better .